Blind at First Sight: The Role of Distinctively Accurate and Positive First Impressions in Romantic Interest. (June 2020) - Kerr, Lauren Gazzard; Tissera, Hasagani; McClure, M. Joy; Lydon, John E.; Back, Mitja D.; Human, Lauren J.
Viewing other people with distinctive accuracy—the degree to which personality impressions correspond with targets' unique characteristics—often predicts positive interpersonal experiences, including liking and relationship satisfaction. Does this hold in the context of first dates, or might distinctive accuracy have negative links with romantic interest in such evaluative settings? We examined this question using two speed-dating samples (Sample 1: N = 172, N = 2, 407 dyads; Sample 2: N = 397, N = 1, 849 dyads). Not surprisingly, positive impressions of potential dating partners were strongly associated with greater romantic interest. In contrast, distinctively accurate impressions were associated with significantly less romantic interest. This association was even stronger for potential partners whose personalities were less romantically appealing, specifically, those lower in extraversion. In sum, on a first date, distinctive accuracy tends to be paired with lower romantic interest. The potential implications of distinctive accuracy for romantic interest and of romantic interest for distinctive accuracy are discussed.